Influences of the Differences Between Mothers’ and Children’s Perceptions of Parenting Styles - Cho, Jiwon; Ha, Jung Hee; Jue, Juliet (Frontiers in Psychology, 2020)
In this study, we explored the differences between mothers’ and children’s perceptions of mothers’ parenting styles (DMCP of MPS), and examined the effects of these differences on children’s depression, aggression, and ego-resilience. A total of 233 pairs of mothers and teen-aged children participated in the study. Our analysis produced four main findings. First, the mothers perceived their parenting attitudes as more rational and affectionate than their children did; children whose mothers rated their parenting styles more favorably had higher levels of depression and aggression and lower ego-resilience. Second, the correlation analysis and the structural equation model verification confirmed that as the DMCP of MPS increased, children’s levels of depression and aggression increased, and their ego-resilience decreased. Third, ego-resilience partly mediated the relationship between DMCP-Rationality and depression. Lastly, we found that ego-resilience and depression had dual mediation effects on the relationship between DMCP-Rationality and children’s aggression. This paper concludes with a discussion of the implications these findings and suggestions for future studies.